Sinus Pericranii in the Left Frontal Region Involving the Superior Eyelid: A Case Report - Grahovac, Gordan; Rajappa, Prajwal; Vilendecic, Milorad; Zic, Rado; Lambasa, Smiljka; Prgomet, Stefan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Sinus pericranii is a rare asymptomatic communication between the intracranial and extracranial venous drainage pathways. The venous flow in this condition circulates through abnormal dilated veins in both directions.Patient/Methods We describe an unusual location of an accessory sinus pericranii that involved the left frontal bone along with the superior orbital rim and the upper eyelid, with special focus on therapy.Results The patient did not have any complication during the first and second surgery. Final outcome was excellent. The patient did not show any evidence of disease recurrence 1 year after the surgery.Conclusion We propose a multidisciplinary approach in the treatment of such lesions with a two-step surgery. Excision of the sinus pericranii is possible if the sinus pericranii is not a major venous outflow channel of the brain, which can be evaluated by angiography.
Keywords: sinus pericranii; orbit; eyelid; dural sinus; vascular tissue